2016
DOI: 10.5114/jcb.2016.63187
|View full text |Cite
|
Sign up to set email alerts
|

Development and clinical implementation of a new template for MRI-based intracavitary/interstitial gynecologic brachytherapy for locally advanced cervical cancer: from CT-based MUPIT to the MRI compatible Template Benidorm. Ten years of experience

Abstract: PurposeTo study outcome and toxicity in 59 patients with locally advanced cervix carcinoma treated with computed tomography (CT)-based Martinez universal perineal interstitial template (MUPIT) and the new magnetic resonance imaging (MRI)-compatible template Benidorm (TB).Material and methodsFrom December 2005 to October 2015, we retrospectively analyzed 34 patients treated with MUPIT and 25 treated with the TB. Six 4 Gy fractions were prescribed to the clinical target volume (CTV) combined with external beam r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
(100 reference statements)
0
16
0
Order By: Relevance
“…However, in the present age of volume-based implants, the use of tandem does not seem to increase the toxicities. Villalba documented 2% grade 3 rectal bleeds with the use of the IC-ISBT system compared with 13% in the ISBT patients (15). Our analysis, too, did not reveal any difference in late sequelae between the two BT techniques ( p 5 0.86).…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…However, in the present age of volume-based implants, the use of tandem does not seem to increase the toxicities. Villalba documented 2% grade 3 rectal bleeds with the use of the IC-ISBT system compared with 13% in the ISBT patients (15). Our analysis, too, did not reveal any difference in late sequelae between the two BT techniques ( p 5 0.86).…”
Section: Discussionmentioning
confidence: 39%
“…(1) It helps in straightening and stabilizing the uterus for the subsequent placement of the needles (1). (2) It addresses the superior intrauterine extension of the tumor, which cannot be accessed adequately with the straight and rigid ISBT needles (15). 3It forms a high-dose region in the cervix, where more resistant tumor cells may reside (2).…”
Section: Discussionmentioning
confidence: 99%
“…1). Nineteen studies met the inclusion criteria and were fully reviewed for data extraction [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Eight studies were excluded after full review: three had no 3D-planning; one used P-ISBT as neoadjuvant treatment, one reported dosimetric outcomes only (no clinical data), one had no primary cervix cancers treated as definitive therapy, one did not use perineal ISBT (intravaginal) and another had a more updated series which was included in our review.…”
Section: Resultsmentioning
confidence: 99%
“…All studies used trans-perineal needles. Plastic catheters were used in nine studies [11,13,15,18,20,22,24,25,30], metallic in five [14,16,17,23,27]. Four studies did not mention needle characteristics [19,21,28,29] and one used either plastic or metallic needles [26].…”
Section: P-isbt Technique Treatment Volume and Dose Prescriptionmentioning
confidence: 99%
“…nous development of applicator and its clinical use has been mentioned previously [10]. A recent survey in India shows that while more than 50% centers use CT as volumetric imaging, 87% centers do not perform any interstitial procedures [11].…”
Section: A B Cmentioning
confidence: 99%